APPLICATION OF MODERN METHODS AND APPROACHES TO TEACHING - Yarmatova Mehriniso Azamatovna (Bright Mind Publishing, 2025)
This article examines key modern teaching methods and their role in improving the quality of education.
Keywords: Project-based learning, gamification, role-playing games, flipped classroom, case method, interactive methods.